METODOLOGI STUDI ISLAM DALAM PEMANFAATAN AI BAGI GURU RUMPUN PAI DI MI - Ahmad Jiyad; Nurma Yunita (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2026)
Abstract This study examines the role of Islamic studies methodology as an epistemological framework in guiding the utilization of artificial intelligence (AI) by Religious Education (Pendidikan Agama Islam/PAI) subject teachers at Madrasah Ibtidaiyah (MI). Employing a qualitative approach through library research, this study systematically analyzes various academic sources related to Islamic studies methodology, AI in education, and PAI learning in Islamic primary schools. The findings reveal that Islamic studies methodology serves as a critical intellectual filter that ensures AI utilization in PAI learning remains grounded in authentic Islamic epistemological standards. This study also identifies significant gaps in AI literacy among PAI teachers and proposes the Tafkir-Taqwim-Tatbiq (T3) conceptual model as a systematic framework for methodologically integrating AI into PAI subject learning. The T3 model positions Islamic studies methodology as the primary epistemological foundation, while AI functions as a supportive instructional tool. This research contributes to the development of contemporary Islamic education that is technologically responsive yet firmly rooted in classical Islamic scholarly traditions. Keywords: Islamic Studies Methodology, Artificial Intelligence in Education, Pendidikan Agama Islam